Answer:
k = 2
Step-by-step explanation:
The equation of function f(x) is:
[tex]f(x)=x^3-4x^2-11x+30[/tex]
To determine the value of k if the graph of f(x) is shifted so that the values of x for which the new graph h(x) = (x+k)³ - 4(x+k)² - 11(x+k) + 30 decreases on the interval -3 < x < 1²/₃, we first need to find the interval on which f(x) decreases.
A function is decreasing when its first derivative is negative.
Differentiate f(x):
[tex]f'(x)=3x^2-8x-11[/tex]
Now set f'(x) < 0:
[tex]f'(x) < 0\\\\3x^2-8x-11 < 0\\\\3x^2+3x-11x-11 < 0\\\\3x(x+1)-11(x+1) < 0\\\\(3x-11)(x+1) < 0[/tex]
As f'(x) is a quadratic function with a positive leading coefficient, its graph will be an upward-opening parabola. Therefore, it will be negative (below the x-axis) between its x-intercepts. The x-intercepts of f'(x) are the x-values when f'(x) = 0. As f'(x) = (3x - 11)(x + 1), then:
[tex]3x-11=0 \implies x=\dfrac{11}{3}\\\\x+1=0 \implies x=-1[/tex]
So, f(x) is decreasing on the interval:
[tex]-1 < x < \dfrac{11}{3}[/tex]
The equation of the new function h(x) is:
[tex]h(x)=(x+k)^3-4(x+k)^2-11(x+k)+30\\\\h(x)=f(x+k)[/tex]
When we add (or subtract) k units to the x-value of a function, it shifts the function k units to the left (or right). Therefore, function h(x) is a horizontal translation of function f(x).
Given that h(x) decreases on the interval -3 < x < 1²/₃, we can find the value of k by comparing this interval to where f(x) is decreasing:
[tex]-1 < x < \dfrac{11}{3} \;\;\longrightarrow \;\;-3 < x < 1\frac23[/tex]
On comparing the two intervals, we can see that h(x) is f(x) shifted 2 units to the left, as evidenced by the left endpoint of the interval on which f(x) is decreasing, x = -1, becoming x = -3. When we shift a function k units to the left, we add k units to its x-value, so the value of k is:
[tex]\Large\boxed{\boxed{k=2}}[/tex]